The role of chain superconductivity in the "123" HTSC: A microscopic approach - I. M. Tang (2018)
A plane-chain model of superconductivity is proposed for the high temperature superconductor YBa2Cu3O7-x. The pair condensation which is assumed to occur in both the 2D CuO2planar sheets and the 1D CuO chains is assumed to be due to the exchanges of the spin fluctuations in sheets and in chains. The carriers in the sheets are coupled to those in the chains by two particle (pair) tunneling. The effect of this coupling on the Tcare examined by looking at the one loop corrections to the Eliashberg equations. The resulting strong coupling expressions for the Tcare very similar to the one previously obtained in a Ginzburg-Landau analysis of the model. © 1998 Elsevier Science Ltd. All rights reserved.